RELEVANCE OF CREATOR’S ECONOMIC RIGHTS PERIOD WITH PUBLIC ACCESS RIGHT IN THE BOOK OF KNOWLEDGE - Roisah, Kholis (Tadulako University, 2018)
Economic rights are creator’s or Copyright holder’s exclusive rights to gain economic advantages over his creation. The history of economic rights in Indonesia continuously experiences changes until the most recent is Copyright Act Number 28 Year 2014 about Copyright of creators’ economic rights is protected for a lifetime plus 70 years after the death of the creator. This change has affected public people, particularly in access to the book of knowledge. This research was conducted using juridical normative method. From the result of the research, it can be concluded that prolonged protection of economic rights causes difficulty for public to access the book of knowledge because public highly depends on books that has become public domain. The book of knowledge is difficult to be accessed because its price tends to be expensive. It is probably useless to wait for the book to be publicly owned because by the time the book is going public, the content will no longer relevant.